The Impact of the Webcam on an Online L2 Interaction - Guichon, Nicolas; Cohen, Cathy (The Canadian Modern Language Review, 2014)
It is intuitively felt that visual cues should enhance online communication, and this experimental study aims to test this prediction by exploring the value provided by a webcam in an online L2 pedagogical teacher-to-learner interaction. A total of 40 French undergraduate students with a B2 level in English were asked to describe in English four previously unseen photographs to a native English-speaking teacher of EFL via Skype, a free web-based videoconferencing tool, during a 10-minute interaction. Twenty students were assigned to the videoconferencing condition and 20 to the audioconferencing condition. All 40 interactions were recorded using dynamic screen capture software and were analyzed with ELAN, a multimodal data annotation tool. Participants’ perceptions of the online interaction are first compared with regard to the issues of social presence and their understanding and appreciation of the online interaction, using data gathered from a post-task questionnaire. The study then explores whether seeing the interlocutor’s image impacts on the patterns of these synchronous exchanges and on the word search episodes. Results indicated that the impact of the webcam on the online pedagogical interaction was not as critical as had been predicted.
Publisher: University of Toronto Press
Keywords: audioconferencing; audioconférence; interaction en ligne; online interaction; présence sociale; recherche lexicale; social presence; videoconferencing; vidéoconférence; word search